Research on the using of ZnO nanostructures to increase the white light-emitting diodes optics effectiveness - Le, Phan Xuan; Cong, Pham Hong (Institute of Advanced Engineering and Science, 2024)
In conventional white light-emitting diodes (WLEDs), the combination of blue-LED chips with a yellow-phosphor type is the commonly employed method of production. However, this approach often results in low angular correlated color temperature (CCT) homogeneity. To address this issue, this research proposes the incorporation of ZnO nanostructures into WLED packages to enhance color homogeneity. The impacts of varying concentrations of ZnO nanoparticles on the morphologies, scattered energy, and CCT deviations in WLED packages are studied utilizing the Mie-scattering theory and MATLAB measurement techniques to analyze the scattering effects of ZnO nanoparticles. The scattering analysis reveals that the presence of ZnO nanoparticles significantly increases the scattered strength of WLEDs, especially with larger particles’ radii, due to their strong scattering influence. Then, 1 µm is the selected size of the ZnO used in further tests. With different ZnO concentrations (2-50 wt.%) in the phosphor layer, the CCT deviation holds an inverse proportion to the luminous efficiency. Particularly, higher concentrations of ZnO nanoparticles reduce the CCT deviation, leading to improved color homogeneity, but a decline in lumen efficiency. The findings provide the basis of ZnO scattering performance, which can be utilized to explore potential ways for enhancing WLED’s color uniformity and overall performance.